Optimization procedures in the problem of marketing educational services at the stage of forming a policy for recruiting applicants to universities - V. A. Rogova; R. V. Shamin (Российский технологический журнал)
The article discusses the optimization procedures in the marketing of educational services in the formation of a marketing strategy for a new recruitment in a university. A mathematical model for formalizing the objective function when evaluating the results of a new recruitment at a university is considered, which is the basis for creating optimization procedures. The results of the new recruitment are characterized by quantitative and qualitative indicators, which include the number of applicants, as well as the average USE score.An economic and mathematical model is proposed for the optimal determination of the parameters of a new set, which provides a balanced policy for implementing a new set. At the same time, the importance of the minimum threshold of USE scores that an applicant must collect for admission to a university is shown. An increase in this parameter contributes to the fact that the average USE score of enrolled students increases, but at the same time the number of students enrolled in places with full cost recovery decreases. An optimization problem is considered, with the help of which it is possible to calculate the optimal value of this parameter.A game-theoretic mathematical model is proposed for modeling the influence of marketing activities and random factors on the result of a new set, with the help of which it is possible to form a ranked list of activities and the optimal allocation of resources. Using the game-theoretic approach allows you to effectively take into account the uncertainties that affect the results of the new set. At the same time, a maximin approach is proposed, with the help of which we calculate the optimal strategy of marketing activities when organizing a new recruitment at a university. At the same time, a general scheme for using the optimization model is proposed and an algorithm is presented with the help of which we obtain a calculated optimal marketing strategy for implementing a new recruitment at a university and an optimal allocation of resources to ensure these activities.